Relationship Parenting Patterns With Level Of Independence Personal Hygiene In Preschool Children In Tk Pertiwi 14.09.01 Poncowarno - Utami, Wuri; Fatimah, Nurul; Iswati, Ning (Prosiding University Research Colloquium, 2022)
Background: Independence of personal hygiene is an action in maintaining personal hygiene, both physical and psychological. One of the factors that can affect the independence personal hygieneof school-age children is parenting. Objective : To determine the relationship between parenting and the level ofindependence personal hygiene stylesin preschool children at Pertiwi Kindergarten 14.09.01 Poncowarno. Methods: This study uses a quantitative correlation method using adesign cross-sectional, the sampling technique uses total sampling with a sample of 65 respondents. The research instrument used was a parenting style questionnaire and a questionnaire on the level ofindependence personal hygiene. Results : The results showed that 44 (67.7%) respondents applied democratic parenting, 14 (21.5%) authoritarian parenting, and 7 (10.8%) permissive parenting patterns. Meanwhile, for the level ofindependence, personal hygiene there were 50 (76.9%) independent children and 15 children (23.1%) quite independent children. Bivariate analysis with chi-square test obtained a p-value of 0.003 which means there is a relationship between parenting patterns and the level ofindependence personal hygiene. Conclusion: The results of this study indicate that there is a significant relationship between parenting patterns and the level ofindependence personal hygiene in preschool children at TK Pertiwi 14.09.01 Poncowarno. Recommendation : Further researchers can use other variables (such as gender) that affect the formation of independence in preschool children.